Filarial breast lump: a rare entity - Kumar, Vinod; Reyaz, Mushir; Singh, Gyanendra (International Surgery Journal, 2018)
Breast filariasis is a rare entity and filarial breast lump can also mimic malignancy. Authors present a case of breast lump from an endemic region which turned out to be a filarial lump on histopathology report. So, a remote diagnosis of filariasis should also be kept in management of patients with breast lump from areas endemic for filariasis to avoid mismanagement.